2019
DOI: 10.1111/pbi.13282
|View full text |Cite
|
Sign up to set email alerts
|

The control of red colour by a family of MYB transcription factors in octoploid strawberry (Fragaria × ananassa) fruits

Abstract: Summary Octoploid strawberry (Fragaria × ananassa Duch.) is a model plant for research and one of the most important non‐climacteric fruit crops throughout the world. The associations between regulatory networks and metabolite composition were explored for one of the most critical agricultural properties in octoploid strawberry, fruit colour. Differences in the levels of flavonoids are due to the differences in the expression of structural and regulatory genes involved in flavonoid biosynthesis. The molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 54 publications
(92 reference statements)
3
87
1
1
Order By: Relevance
“…An independent missense mutation, famyb10-1, was also found in this study for lines with white skin color from UF breeding population 17.66. The mutation is same as a previously identified INDEL (Wang et al, 2020). Our study precisely located this mutation to the dominant homoeologous allele on Fvb1-2 and showed that it controls fruit skin color.…”
Section: Transient Overexpression Ofsupporting
confidence: 68%
See 3 more Smart Citations
“…An independent missense mutation, famyb10-1, was also found in this study for lines with white skin color from UF breeding population 17.66. The mutation is same as a previously identified INDEL (Wang et al, 2020). Our study precisely located this mutation to the dominant homoeologous allele on Fvb1-2 and showed that it controls fruit skin color.…”
Section: Transient Overexpression Ofsupporting
confidence: 68%
“…Deletion of the 54 C-terminal residues may render FaMYB10 inactive. In fact, this same polymorphism was recently shown to be associated with white fruits in 'Snow Princess', and restoration of anthocyanin biosynthesis was only possible by over-expression of WT MYB10 (Wang et al, 2020). The presence of the same mutation, hereafter named famyb10-1, suggests that the white-fruited selection FL 14.29-1 and 'Snow Princess' may share a common pedigree.…”
Section: Myb10 Allelic Variants In White-fruited Octoploid Accessionsmentioning
confidence: 93%
See 2 more Smart Citations
“…To date, various MYB transcription factors and the MYB/bHLH/WD-repeat protein complex are known to regulate anthocyanin biosynthesis in strawberry (Salvatierra et al 2013; Schaart et al, 2013; Medina-Puche et al 2014; Wang et al 2020). The best studied strawberry MYB is MYB10, whose mutation induces a loss of red fruit colour in the cultivated strawberry and in the wild diploid species F. vesca and F. nilgirensis (Medina-Puche et al 2014; Hawkins et al 2016; Wang et al 2020; Castillejo et al 2020; Zhang et al 2020). However, the most likely MYB candidate gene underlying the female F3a pelargonidin-3-glucoside mQTL is not homologous to a well characterized strawberry MYB.…”
Section: Discussionmentioning
confidence: 99%